2013
DOI: 10.5812/ircmj.14254
|View full text |Cite
|
Sign up to set email alerts
|

The Bridge Between real and Ideal: Students Perception on Quality Gap in Reality and Their Educational Expectations

Abstract: Background:Studies in higher education indicated that students’ expectation for their educational services are not provided sufficiently, particularly in developing countries that implies on gap between the students perception on current situation and their expectations from educational services.Objectives:The aim of this study was to determine the gap between student perception and expectations of students in various levels of the undergraduate educational courses at Urmia University of Medical Sciences, Iran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 12 publications
1
14
0
Order By: Relevance
“…Therefore, it appears that educational services in all aspects need to be reviewed and reformed. Similar studies in other Iranian medical universities so far have reported a negative gap in all dimensions (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). In a metaanalysis review conducted in 2019 using the SERVQUAL assessment model for the student satisfaction in Iranian medical universities, there was a negative gap in all five dimensions.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Therefore, it appears that educational services in all aspects need to be reviewed and reformed. Similar studies in other Iranian medical universities so far have reported a negative gap in all dimensions (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). In a metaanalysis review conducted in 2019 using the SERVQUAL assessment model for the student satisfaction in Iranian medical universities, there was a negative gap in all five dimensions.…”
Section: Discussionsupporting
confidence: 78%
“…By defining the gap in quality of services, programs can be developed for promoting the quality of education (2). The results of several studies conducted among the Iranian medical students showed that there is a gap in all five dimensions of quality of educational services (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Similar studies carried out among some universities outside Iran have also reported a gap in all dimensions (22)(23)(24)(25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%
“…The results of other studies on the quality of hospital services also suggest a negative gap between all dimensions of patients' and service receivers' expectations and perceptions of the quality of the services provided [21][22][23][24][25][26]. Moreover, studies conducted in teaching and educational centers in this field have reported a negative gap between all dimensions [27][28][29][30][31][32][33]. A negative gap means that the current quality from the viewpoint of the users of the centers is estimated to be lower than their expectation or desired status.…”
Section: Discussionmentioning
confidence: 99%
“…With regards to the score of the consumers' perception of service quality, the highest score was related to "assurance" (3.82) and lowest score was related to "empathy" (3.57). Other conducted studies have also reported "assurance" as the dimension with the highest score [22,24,25,27,29,35]. The mean score of "empathy" can be increased through taking some actions; for example, understanding and paying attention to users' and patients' needs and requirements, respecting their beliefs and cultural values, creating empathy and bonding with individuals, making a proper emotional connection, as well as paying attention to their personal needs.…”
Section: Discussionmentioning
confidence: 99%
“…This study is aimed to introduce a reasonably effective tool in the form of ananonymous performa completed by individual students is an attempt to fill this void in assessment.This will be of no point value which is recommended for summative assessment. Existence of gaps over student expectations of many different aspects in teaching-learning encounters employed need to be addressed to prevent dissatisfaction (2).…”
Section: Discussionmentioning
confidence: 99%